THE USE OF VIDEO IN TEACHING SPEAKING TO YOUNG LEARNERS - Putri Rahayu Ningsih, - (2012)
This study investigates how the video improves children's speaking ability, the types of speaking that are produced by children, and the aspects of speaking that are improved by using video. It employed classroom action research design and involved five young learner students aged seven to eight-year old children in young learners' classroom as the subjects. In order to gain the desired data, observation, audio recording, and interview were conducted. The data were obtained from observation in which children learn English during 3 cycles by using video. The observation data that were related to the types of speaking that were produced by children were analyzed with reference to the framework from Brown (2001), while the aspects of speaking that were improved by using video were analyzed with reference to the framework by Linse (2005). This study indicated that there were some improvements of children's speaking ability. The data gained from assessment showed that children's score were gradually improved in terms of pronunciation, vocabulary, fluency and grammar. In addition, the data gained from observation indicated that there were three types of speaking that were produced by children. Those were imitative, responsive, and intensive. Based on the result of the study, it is recommended for teachers that video be implemented in teaching speaking especially for young learners using speaking activities mentioned in the reflective cycle.